Effects of Bariatric Surgery in Obese Patients With Hypertension: The GATEWAY Randomized Trial (Gastric Bypass to Treat Obese Patients With Steady Hypertension). Issue 11 (13th March 2018) - Schiavon, Carlos Aurelio; Bersch-Ferreira, Angela Cristine; Santucci, Eliana Vieira; Oliveira, Juliana Dantas; Torreglosa, Camila Ragne; Bueno, Priscila Torres; Frayha, Julia Caldas; Santos, Renato Nakagawa; Damiani, Lucas Petri; Noujaim, Patricia Malvina; Halpern, Helio; Monteiro, Frederico L.J.; et al.
Abstract : Background: Recent research efforts on bariatric surgery have focused on metabolic and diabetes mellitus resolution. Randomized trials designed to assess the impact of bariatric surgery in patients with obesity and hypertension are needed. Methods: In this randomized, single-center, nonblinded trial, we included patients with hypertension (using ≥2 medications at maximum doses or >2 at moderate doses) and a body mass index between 30.0 and 39.9 kg/m 2 . Patients were randomized to Roux-en-Y gastric bypass plus medical therapy or medical therapy alone. The primary end point was reduction of ≥30% of the total number of antihypertensive medications while maintaining systolic and diastolic blood pressure <140 mm Hg and 90 mm Hg, respectively, at 12 months. Results: We included 100 patients (70% female, mean age 43.8±9.2 years, mean body mass index 36.9±2.7 kg/m2), and 96% completed follow-up. Reduction of ≥30% of the total number of antihypertensive medications while maintaining controlled blood pressure occurred in 41 of 49 patients from the gastric bypass group (83.7%) compared with 6 of 47 patients (12.8%) from the control group with a rate ratio of 6.6 (95% confidence interval, 3.1–14.0; P <0.001). Remission of hypertension was present in 25 of 49 (51%) and 22 of 48 (45.8%) patients randomized to gastric bypass, considering office and 24-hour ambulatory blood pressure monitoring, respectively, whereas no patient submitted to medical therapy was free of antihypertensive drugs at 12 months. A post hoc analysis for the primary end point considering the SPRINT (Systolic Blood Pressure Intervention Trial) target reached consistent results, with a rate ratio of 3.8 (95% confidence interval, 1.4–10.6; P =0.005). Eleven patients (22.4%) from the gastric bypass group and none in the control group were able to achieve SPRINT levels without antihypertensives. Waist circumference, body mass index, fasting plasma glucose, glycohemoglobin, low-density lipoprotein cholesterol, triglycerides, high-sensitivity C-reactive protein, and 10-year Framingham risk score were lower in the gastric bypass than in the control group. Conclusions: Bariatric surgery represents an effective strategy for blood pressure control in a broad population of patients with obesity and hypertension. Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT01784848. Abstract : Supplemental Digital Content is available in the text.